Secularism, assimilation and the crisis of multiculturalism: French modernist legacies - Jansen, Yolande (IMISCOE research, 2013)
The crisis of multiculturalism, new assimilationism and secularism -- Assimilation in the French sociology of incorporation from a multicultural perspective -- The liberal sociology of assimilation and citizenship and its transnationalist alternatives -- Proust as a witness of assimilation in 19th-century France -- Alfred Bloch's personal integration test at the threshold of his friend's home -- Stuck in a revolving door -- Loïcité and assimilation in the Third Republic and today -- Elements of a critique of the Loïcité-religion framework -- Secularism, sociology and security -- The highly precarious structure of assimilation : modernist philosophical schemes, memory and the Proustian narrative